Construção de uma escala para avaliação de prejuízos em adultos com o transtorno de déficit de atenção/hiperatividade - Ana Paula Assis de Oliveira (2016)
The attention-deficit/hyperactivity disorder is one of the most well studied psychiatric disorders being defined as a neurodevelopment disorder that presents as a fundamental characteristic, persistent pattern of inattention and/or hyperactivity which impacts the functioning and development. Considering this definition last aspect, ie, the functional impairment, it constitutes one of the required criteria for the diagnosis establishing of several mental disorders and can be understood as the difficulty degree in interaction, experienced by people, with their development contexts and its adverse consequences. However, there are few instruments to assess them rigorously and quantitatively. This study aimed to build a self-report scale to specifically assessing the impairments that adults with attention-deficit/hyperactivity disorder experience in important life areas and collect validity evidence. The scale was entitled Functional Impairment Scale (FIS-ADHD), structured in two parts. The first exploring more specifically difficulties that adults often experience in several areas of functioning and the second part investigating the general perception that the respondent has on the exploited areas. In its final version, the FIS-ADHD was composed of 75 items. Their development process was consisted of seven stages, namely: constitutive definition of impairment and selection of areas through theoretical review/experts, interview with the target population, construction of items / instrument, analysis of judges, semantic analysis, application of FIS-ADHD and psychometric analysis. Participants were 1589 adults with and without the condition of interest, of both sexes, with different levels of education, living in different regions of Brazil, aged between 18 and 76 years. The data were submitted to confirmatory factor analysis, based on a hierarchical hypothetical model and nine factors derived from the exploratory factor analysis. The analysis indicated the appropriateness of both models, with adjustment quality scores very close, providing empirical evidence of the appropriateness of the model designed for the scale.The internal consistency has a high degree of reliability (0.97 total set; 0.78 to 0.92 per area). The mean of raw score showed a significant difference between the clinical group and the control group in all nine assessed areas specifically and in general in both parts of scale. Based on these results, it can be considered as satisfactory the psychometric properties of the new instrument. Thus, it is concluded that the FIS-ADHD attends its proposal to assess the impairments in adults with attention-deficit/hyperactivity disorder and proved to be useful to the clinical and research contexts.